2014
DOI: 10.1007/s00464-014-3772-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic sphincter augmentation and fundoplication for GERD in clinical practice: one-year results of a multicenter, prospective observational study

Abstract: Antireflux surgery should be individualized to the characteristics of each patient, taking into consideration anatomy and propensity and tolerance of side effects. Both MSAD and LF showed significant improvements in reflux control, with similar safety and reoperation rates. In the treatment continuum of antireflux surgery, MSAD should be considered as a first-line surgical option in appropriately selected patients without Barrett's esophagus or a large hiatal hernia in order to avoid unnecessary dissection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 22 publications
(18 reference statements)
7
60
0
2
Order By: Relevance
“…Despite this, insurance carriers have been hesitant to cover MSA as a surgical option for GERD, either due to concerns over perceived additional costs of the procedure or due to the lack of comparative studies to the traditional surgical treatment for GERD. Several recent comparative studies including this one have now definitively shown that MSA is equally effective as LNF in symptom control and PPI elimination rates [5,6,12]. Additionally, in this analysis of MSA versus LNF, we found that MSA patients had less gas bloat symptoms and increased ability to belch and vomit.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Despite this, insurance carriers have been hesitant to cover MSA as a surgical option for GERD, either due to concerns over perceived additional costs of the procedure or due to the lack of comparative studies to the traditional surgical treatment for GERD. Several recent comparative studies including this one have now definitively shown that MSA is equally effective as LNF in symptom control and PPI elimination rates [5,6,12]. Additionally, in this analysis of MSA versus LNF, we found that MSA patients had less gas bloat symptoms and increased ability to belch and vomit.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown MSA to be safe and effective with PPI elimination rates, pH normalization, and symptom control similar to that reported for LNF [1][2][3][4][5][6][7]. However, the device has only been approved for a few years and many payers are hesitant to cover the cost of the procedure over continued concerns about long-term outcomes, potential side effects, and the cost of the device, which averages $5000.…”
mentioning
confidence: 58%
“…There were two retrospective case-control studies 11,12 and a prospective control study 13 taken into consideration for the review. A total of 688 patients were identified, and 273 patients had undergone LNF; 415 patients went for LINX MSA.…”
Section: Resultsmentioning
confidence: 99%
“…Major morbidity of LNF included intraoperative pleural injury, 13 formation of retropharyngeal abscesses, 12 and four cases were subjected to a revision surgery due to hiatal hernia recurrence. 12,13 The MSA group morbidity included one pleural injury, two incidences of intra operative bleeding, one pneumothorax, 13 and one gastroesophageal obstruction. 12 Two patients had their device removed, one had treatment failure, and the other patient had dysphagia secondary to device erosion 18 months after the surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, this topic was addressed in a prospective multicenter trial with participation of our institution [29]. Riegler et al analyzed magnetic sphincter augmentation versus laparoscopic fundoplication.…”
Section: Magnetic Sphincter Augmentationmentioning
confidence: 99%